Perception of body image and control center patterns for girls who are late in marriage (Journal of Human Sciences, 2021)
The current study aimed to identify the nature of the relationship between perception of body image (positive-negative) and patterns of control center (internal - and external) in marriage arrears, and to know the differences between the perception of body image and pattern of control center according to some demographic variables, namely, Gregorian arrangement) in light of theories of causal attribution. The sample of the study consisted of (14) single women, the personal selection was made from the cities of Al-Bayda, Al-Qobba, Derna, who met the conditions of age (over 24 to 47) years, and the civil status (single). The body image scale was applied to the numbers of Zainab Choucair (2002), the control center scale was the number of Roter and Arabization (Aladdin Kafafi, 1982) The psychometric properties of the scales were confirmed. After analyzing the data using statistical methods, including the Pearson correlation coefficient and the test (T), and the descriptive approach. The study reached the following main results:There is a negative correlation between the perception of body image and the pattern of the center of control in the single category as a whole.There are statistically significant differences between the single women in the pattern of the center of the internal control and the pattern of the center of the external control in favor of women with the pattern of the center of the external control.- The absence of differences between those with the center of the external control pattern and those with the pattern of the center of the internal control in perceiving the image of the body (positive).